Evoking the Sublime in Landscape Painting: Joseph Anton Koch’s Schmadribachfall and Caspar David Friedrich’s Watzmann - Scherbaum, Sonja (Aesthetica Preprint, 2024)
Kant’s rejection of the possibility of an artistic sublime requires critical revision. By reference to two landscape paintings – Joseph Anton Koch’s Schmadribachfall and Caspar David Friedrich’s Watzmann – it will be shown that paintings can indeed be capable of evoking an experience of the sublime. In this context, it is precisely the painting’s manner of representation that can provoke the failure of apprehension and comprehension that is central to the mathematically sublime and that represents an indispensable element of the experience of the sublime. Although Immanuel Kant cites examples from architecture to illustrate this failure of apprehension and comprehension, a pure judgment of the sublime can only be made regarding “raw nature”. Works of art, however, are always determined in their form and size by a human purpose. On the basis of contemporary sources, it will be shown that works of art can be considered as mere magnitudes. Another reason for Kant’s rejection of the artistic sublime is his restrictive understanding of the work of art. The historical analysis of the paintings in question will show that beyond the level of this normative understanding of the work of art, paintings can be capable of eliciting an experience of the sublime.